PENGEMBANGAN MEDIA PEMBELAJARAN AUGMENTED REALITY TATA SURYA (ARTAS) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS VI SD - Veronika Cinda; Adi Winanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Science learning in elementary school requires innovative learning media that can improve concept understanding in an interactive and interesting way. This research aims to: (1) produce Solar System Augmented Reality (ARTAS) learning media that can improve science learning outcomes of grade VI elementary school students, (2) determine the feasibility of ARTAS media in supporting learning, and (3) find out the effectiveness of these media in improving science learning outcomes. This research uses the Research and Development (R&D) method with the ADDIE development model which includes the stages of analysis, design, development, implementation, and evaluation. ARTAS media was developed using the marker-based Assemblr EDU platform accessed via QR code, which displays solar system objects in the form of digital interactive 3D models into the real world. The validation results showed that this media is very feasible to use, with a feasibility value of 94% by material experts and 94,11% by media experts. The results of the effectiveness test showed that the use of ARTAS media was able to improve the science learning outcomes of grade VI elementary school students with a percentage of 79,1% which was included in the effective category. This study concludes that ARTAS media is a technology-based learning media that is feasible and effective in science learning to support the improvement of student learning outcomes.